2020
DOI: 10.1002/nbm.4458
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing echo and repetition times in magnetic resonance imaging using a double half‐echo k‐space acquisition and low‐rank reconstruction

Abstract: Sampling k‐space asymmetrically (ie, partial Fourier sampling) in the readout direction is a common way to reduce the echo time (TE) during magnetic resonance image acquisitions. This technique requires overlap around the center of k‐space to provide a calibration region for reconstruction, which limits the minimum fractional echo to ~60% before artifacts are observed. The present study describes a method for reconstructing images from exact half echoes using two separate acquisitions with reversed readout pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In the present study, we found that there was no significant difference in the SNR of SLI lesions; however, the CNR of the images from the ACS acceleration method was significantly higher than that of the conventional T2-FLAIR images, which also indicates that the ACS technique can avoid technical defects, including the Gibbs artifact, SNR reduction, noise amplification, and residual blending caused by acceleration methods, such as HF, PI, and CS (24)(25)(26)(27)(28). Therefore, the accuracy of the diagnosis is also ensured.…”
Section: Discussionsupporting
confidence: 40%
“…In the present study, we found that there was no significant difference in the SNR of SLI lesions; however, the CNR of the images from the ACS acceleration method was significantly higher than that of the conventional T2-FLAIR images, which also indicates that the ACS technique can avoid technical defects, including the Gibbs artifact, SNR reduction, noise amplification, and residual blending caused by acceleration methods, such as HF, PI, and CS (24)(25)(26)(27)(28). Therefore, the accuracy of the diagnosis is also ensured.…”
Section: Discussionsupporting
confidence: 40%
“…Sampling an echo fraction below 60% of each k-space line has been shown to induce artifacts without the DHE low-rank framework. 22 Both k-space halves were jointly reconstructed using low-rank coupling and added sparsity. Two reconstructed k-space halves were obtained and combined via the sum of squares method.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…This technique requires obtaining two k-space halves, which are retrospectively combined by enforcing low-rankness along the k-space rows. 22 In parallel, acceleration techniques that optimally leverage the highly multidimensional structure of 23 Na MQC MRI are warranted to reduce long acquisition times and the associated limitations in spatial resolution. Low-rank reconstruction has proven applicable to highly redundant 1 H multichannel MRI data.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, their accuracy of both image phase and magnitude estimations is suboptimal especially in presence of rapid local phase changes, exhibiting severe image artifacts and preventing the use of low PF fractions. 10,11 This limitation is particularly true for GRE based imaging and phase-sensitive imaging protocols. 4,5 Recently, deep learning using convolutional neural networks (CNNs) has emerged as a powerful computational tool in various aspects of MR image formation, including image reconstruction, artifacts reduction, and noise suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods can often effectively reconstruct full‐resolution magnitude images, they cannot provide detailed phase information. Consequently, their accuracy of both image phase and magnitude estimations is suboptimal especially in presence of rapid local phase changes, exhibiting severe image artifacts and preventing the use of low PF fractions 10,11 . This limitation is particularly true for GRE based imaging and phase‐sensitive imaging protocols 4,5 …”
Section: Introductionmentioning
confidence: 99%